An Overview of Emotion Regulation in Early Adult Victims of Infidelity in the Dating Period - Regina Yusvanila Vebiani; Yusni Berti Nauly Mendrofa; Rina Mirza; Achmad Irvan Dwi Putra; Merri Hafni (Dinasti International Journal of Education Management And Social Science, 2025)
This study reviews the description of emotional regulation in early adult victims of infidelity in the dating period. This type of research is phenomenological qualitative research using interview techniques. The subjects of this study amounted to 4 people, who were obtained using purposive sampling technique. The characteristics of the research subjects are individuals with an early adult age range of 18-25 years, have experienced infidelity and live in Binjai, North Sumatra. The results of this study indicate that the four subjects experienced different emotions and emotional regulation during and after infidelity. When experiencing infidelity, the emotions felt by the subjects were anger, upset, sadness, heartache and disappointment. After experiencing infidelity, there were several other emotional reactions felt by the subject such as sadness, disappointment, annoyance, anger, frustration, despair, aggression, hatred, disgust and desire for revenge. In addition, the subject also felt positive emotions such as comforted, happy, satisfied, relieved, optimistic, enthusiastic, enthusiastic, accepting and grateful, but these positive emotional reactions did not appear as much as negative emotions. Emotion regulation is carried out through 5 stages, namely situation selection, situation modification, attention deployment, cognitive change, and response modulation. In addition, this study also shows that the subject's emotion regulation ability is influenced by social support, gender, self-concept, parenting and attachment style with the mother. Emotion regulation ability can be improved by self-talk and journaling. .